The Impact of Different Length of Operating Cycle on Saudi Cement Corporations’ Performance: An Applied Study - Hamoudah, Manal Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
This study examined the impact of different length of operating cycle (the sum of the average inventory period and average collection period) on the profitability and earnings quality of Saudi Cement corporations listed in Saudi Arabia Stock exchange during five years from 2016 to 2020. In addition, current ratio, net profit, and company age were used as control variables. The study used Return on Asset (ROA) and Return on Assets from Operating Cash Flow (ROAFOCF) as proxies to measure profitability and earnings quality. To achieve the aims of the study, data were obtained from the annual financial reports published in the “Tadawul”, for a purposive sample of fourteen (14) companies. Descriptive statistics, Two Way Anova, Pearson’s Linear Correlation and Simple regression analysis were used to test the hypotheses of the study. The results indicated that ROA and ROAFOCF have been explained at 61%, and 56% respectively. Furthermore, the results found that the length of operating cycle and current ratio have a negative and statistically significant effect on ROA. However, while the results found that the length of operating cycle has a negative and statistically significant effect on ROAFOCF, it did not find any significant effect of current ratio on ROAFOCF. Based on the results, we recommend that corporations need to pay attention to shorten the length of operating cycle in more efficient ways, especially through increasing the level of sales, which in turn lead to improve firm profitability and earnings quality.
Keywords: length of operating cycle; profit quality; corporate profitability; Saudi cement sector